United States : 2003 Article IV Consultation-Staff Report; Staff Supplement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2003)
Despite repeated shocks, the United States economy has provided valuable support for global growth. Executive Directors commended this development, and stressed the need to tighten fiscal and monetary policies. They welcomed the assessment of the fiscal transparency Reports on Observance of Standards and Codes that the United States has set in areas of fiscal transparency. They urged the authorities to strengthen the financial position of the Social Security and Medicare system. They demanded the United States to play a leadership role in promoting an open multilateral trade system.